Advance on iron overload in liver diseases - LIU Lei, DING Lan, YUAN Yuan, YE Jing (Jichu yixue yu linchuang, 2023)
Iron is essential for living organisms. Iron-containing proteins play a key role in cell function, while iron overload produces reactive oxygen species through electron transfer, resulting in DNA damage, oxidative stress, metabolic disorder and tissue as well as organ dysfunction. Liver is the main organ of iron storage and is related to regulating the metabolism, utilization and excretion of iron and maintaining iron homeostasis. Iron overload is common in patients with liver diseases, which is closely related to the occurrence and development of liver diseases.